Magnetic resonance imaging and ultrasound elastography in the context of preclinical pharmacological research: significance for the 3R principles - Obrecht, Michael; Zurbruegg, Stefan; Accart, Nathalie; Lambert, Christian; Doelemeyer, Arno; Ledermann, Birgit; Beckmann, Nicolau (Frontiers in Pharmacology, 2023)
Preclinical research within drug discovery still relies to a great extent on the availability of animal models of disease. Minimizing the distress as well as reducing the number of animals in experimental studies is of outmost importance and remains a constant objective in this area. Due to its noninvasive character in vivo imaging supports this effort by enabling longitudinal assessments in which each animal serves as its own control, thereby enabling to reduce considerably the animal utilization in the experiments. Moreover, imaging has translational prospects by facilitating the comparison of studies performed in small rodents and humans. Also learnings from the clinic may be potentially back-translated to preclinical settings and therefore contribute to refining animal investigations. By concentrating primarily on activities around the application of magnetic resonance imaging (MRI) and ultrasound elastography to small rodent models of disease, we aim to illustrate here how in vivo imaging contributes to reduction and refinement in the context of pharmacological research.The 3Rs principles -reduction, refinement, replacement -are at the core of preclinical research within drug discovery, which still relies to a great extent on the availability of models of disease in animals. Minimizing their distress, reducing their number as well as searching for means to replace them in experimental studies are constant objectives in this area. Due to its non-invasive character in vivo imaging supports these efforts by enabling repeated longitudinal assessments in each animal which serves as its own control, thereby enabling to reduce considerably the animal utilization in the experiments. The repetitive monitoring of pathology progression and the effects of therapy becomes feasible by assessment of quantitative biomarkers. Moreover, imaging has translational prospects by facilitating the comparison of studies performed in small rodents and humans. Also, learnings from the clinic may be potentially back-translated to preclinical settings and therefore contribute to refining animal investigations. By concentrating on activities around the application of magnetic resonance imaging (MRI) and ultrasound elastography to small rodent models of disease, we aim to illustrate how in vivo imaging contributes primarily to reduction and refinement in the context of pharmacological research.